Transcriptomic analysis of spinal cord regeneration after injury in Cynops orientalis - Di Wang; Man Zhao; Xiao Tang; Man Gao; Wenjing Liu; Minghui Xiang; Jian Ruan; Jie Chen; Bin Long; Jun Li (Neural Regeneration Research, 2023)
[INLINE:1] Cynops orientalis (C. orientalis) has a pronounced ability to regenerate its spinal cord after injury. Thus, exploring the molecular mechanism of this process could provide new approaches for promoting mammalian spinal cord regeneration. In this study, we established a model of spinal cord thoracic transection injury in C. orientalis, which is an endemic species in China. We performed RNA sequencing of the contused axolotl spinal cord at two early time points after spinal cord injury – during the very acute stage (4 days) and the subacute stage (7 days) – and identified differentially expressed genes; additionally, we performed Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses, at each time point. Transcriptome sequencing showed that 13,059 genes were differentially expressed during C. orientalis spinal cord regeneration compared with uninjured animals, among which 4273 were continuously down-regulated and 1564 were continuously up-regulated. Down-regulated genes were most enriched in the Gene Ontology term “multicellular organismal process” and in the ribosome pathway at 10 days following spinal cord injury. We found that multiple genes associated with energy metabolism were down-regulated and multiple genes associated with the lysosome were up-regulated after spinal cord injury, indicating the importance of low metabolic activity during wound healing. Immune response-associated pathways were activated during the early acute phase (4 days), while the expression of extracellular matrix proteins such as glycosaminoglycan and collagen, as well as tight junction proteins, was lower at 10 days post-spinal cord injury than 4 days post-spinal cord injury. However, compared with 4 days post-injury, at 10 days post-injury neuroactive ligand-receptor interactions were no longer down-regulated, up-regulated differentially expressed genes were enriched in pathways associated with cancer and the cell cycle, and SHH, VIM, and Sox2 were prominently up-regulated. Immunofluorescence staining showed that glial fibrillary acidic protein was up-regulated in axolotl ependymoglial cells after injury, similar to what is observed in mammalian astrocytes after spinal cord injury, even though axolotls do not form a glial scar during regeneration. We suggest that low intracellular energy production could slow the rapid amplification of ependymoglial cells, thereby inhibiting reactive gliosis, at early stages after spinal cord injury. Extracellular matrix degradation slows cellular responses, represses the expression of neurogenic genes, and reactivates a transcriptional program similar to that of embryonic neuroepithelial cells. These ependymoglial cells act as neural stem cells: they migrate and proliferate to repair the lesion and then differentiate to replace lost glial cells and neurons. This provides the regenerative microenvironment that allows axon growth after injury.